2003
DOI: 10.1002/mrm.10368
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative HRMAS proton total correlation spectroscopy applied to cultured melanoma cells treated by chloroethyl nitrosourea: Demonstration of phospholipid metabolism alterations

Abstract: The ability to follow phospholipid (Plp) metabolism is of paramount importance in many circumstances in which cell survival and cell proliferation are of concern-for example in neurological disorders and cancer (1,2). NMR spectroscopy has long been known to be important tool for exploring Plp metabolism (3-6). Novel NMR developments, such as high-resolution magic angle spinning (HRMAS) probes, have provided improved spectra of cultured cells (7) and normal (8,9) and cancer (10 -12) tissues. Recently, using HRM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 24 publications
1
57
0
Order By: Relevance
“…PUF accumulation may result from hydrolysis of membranes [28], inhibition of PUF consumption, or inhibition of cyclooxygenase-2 (COX-2) activity [29]. Actually, taxanes have been shown to yield mobile lipid formation [28,30] and variations of phospholipid metabolism derivatives [31], although not specifically among antineoplastic agents [28,[32][33][34]. PUF levels may relate an autophagic process implicating damaged membranes [30].…”
Section: Discussionmentioning
confidence: 99%
“…PUF accumulation may result from hydrolysis of membranes [28], inhibition of PUF consumption, or inhibition of cyclooxygenase-2 (COX-2) activity [29]. Actually, taxanes have been shown to yield mobile lipid formation [28,30] and variations of phospholipid metabolism derivatives [31], although not specifically among antineoplastic agents [28,[32][33][34]. PUF levels may relate an autophagic process implicating damaged membranes [30].…”
Section: Discussionmentioning
confidence: 99%
“…Quantification was performed on an O2 workstation (Silicongraphics) using the built-in deconvolution software (XWIN-NMR v2.6, Bruker), and normalization was performed relative to the water signal as already reported. 22 Measured derivatives included phosphoethanolamine (PE) (CH 2 signal at 3.99 ppm), phosphatidylcholine (PtdCho) (N(CH 3 ) 3 broad signal at 3.26 ppm), taurine (Tau) (CH 2 signal at 3.43 ppm), glycine (Gly) (CH 2 signal at 3.56 ppm), lysine (Lys) (e-CH 2 signal at 3.00 ppm), total creatine (tCr) (CH 2 signal at 3.93 ppm), lactate (Lac) (CH 3 signal at 1.33 ppm), alanine (Ala) (CH 3 signal at 1.47 ppm). Also total glutathione (GSx 5 reduced 1 oxidized glutathione) (CH 2 signal at 2.55 ppm) was quantified.…”
Section: Proton High Resolution Magic Angle Spinning Nmr Spectroscopymentioning
confidence: 99%
“…We previously reported that B16 melanoma cells responded to chloroethylnitrosourea (CENU)-induced DNA damage (11), by G 2 /M cell cycle arrest, biopolar spindle blockade, glycolysis downregulation followed by adaptative and/or redifferentiation processes (12,13). This suggested the inhibition of the Akt/PKB pathway as a possible consequence of PP2A activation in response to DNA damage.…”
Section: Introductionmentioning
confidence: 99%